2015
DOI: 10.1007/s00216-015-8487-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modification sites in glycated crystallin in vitro and in vivo

Abstract: Glycation of α-crystallin is responsible for age- and diabetic-related cataracts, which are the main cause of blindness worldwide. We optimized the method of identification of lysine residues prone to glycation using the combination of LC-MS, isotopic labeling, and modified synthetic peptide standards with the glycated lysine derivative (Fmoc-Lys(i,i-Fru,Boc)-OH). The in vitro glycation of bovine lens α-crystallin was conducted by optimized method with the equimolar mixture of [12C6]- and [13C6]d-glucose. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Another informative labeling technique relies on incubation with [ 13 C 6 ]glucose under the conditions mimicking in vivo glycation [ 131 , 151 , 221 ]. In terms of this approach, relative quantification relied on doublet signals representing in vivo glycation with [ 12 C 6 ]glucose and in vitro incorporation of [ 13 C 6 ]glucose [ 131 , 151 , 250 ]. Finally, standard isotope dilution techniques might rely on synthetic 13 C, 15 N-labeled peptides, spiked to plasma samples for a high-throughput characterization of their glycated profiles by multiple reaction monitoring [ 189 ].…”
Section: Part 1 Probing the Structure Of Glycated Proteins By Masmentioning
confidence: 99%
“…Another informative labeling technique relies on incubation with [ 13 C 6 ]glucose under the conditions mimicking in vivo glycation [ 131 , 151 , 221 ]. In terms of this approach, relative quantification relied on doublet signals representing in vivo glycation with [ 12 C 6 ]glucose and in vitro incorporation of [ 13 C 6 ]glucose [ 131 , 151 , 250 ]. Finally, standard isotope dilution techniques might rely on synthetic 13 C, 15 N-labeled peptides, spiked to plasma samples for a high-throughput characterization of their glycated profiles by multiple reaction monitoring [ 189 ].…”
Section: Part 1 Probing the Structure Of Glycated Proteins By Masmentioning
confidence: 99%
“…Simulation studies have shown that, although Trp 60 is exposed to solvent in the α-B subunit, it is buried in the dimer models, located at the interacting interface of the subunits (Guo 2008). Using LCMS and isotopic labeling, Kielmas et al (2015) have shown that K70, K88, K92, K99, K103, K145, K150 and K166 are the lysine glycation targets on α-crystallin. Gangadharaiah et al (2010) have reported that R12, R21, R54, R65, R69, R103, R112, R117, R119, R157 and R163 are arginine glycation sites on α-crystallin.…”
Section: Resultsmentioning
confidence: 98%
“…26 In a more recent study, several lysine modification sites were identified by LC-MS and confirmed by comparison with synthetic standards containing fructoselysine. 27 The chemical structures of many AGEs and their effects on protein structure and function, however, are still unknown. In this study, we identify a DHA modification on the side chain of arginine residues in peptides that occurs during CuAAC ligations in the presence of high concentrations of ascorbate.…”
Section: Methodsmentioning
confidence: 99%